The Effectiveness Of Google Classroom and Dojo Class Using the Discovery Learning Model on The Learning Outcomes of Vocational School Students - Suswanto, Hary; Soraya, Dila Umnia; Ramadiani, Nanda Resta; Utomo, Wahyu Mulyo (Letters in Information Technology Education (LITE), 2022)
The aims of this study were to determine: (1) student learning outcomes through the use of Google Classroom and Class Dojo with the discovery learning model and (2) the effectiveness and efficiency of using Google Classroom and Class Dojo with the discovery learning model for class X. Multimedia students at SMKN 7 Poor. This research is a quasi-experimental research with quantitative and qualitative methods with the design of "Pre-test Post-test Nonequivalent Control Group". Data collection techniques by conducting interviews, giving treatment during learning, and student response questionnaires. The hypothesis is obtained from efficiency test data and effectiveness test. The results obtained from this study are: (1) the implementation of learning using Google Classroom and Class Dojo with the discovery learning model has increased learning outcomes and (2) the use of Google Classroom and Class Dojo with the discovery learning model provides efficient and effective results. In terms of efficiency and effectiveness, learning using Class Dojo with the discovery learning model is more efficient and effective compared to Google Classroom.